A meta-analysis of the validity of FFQ targeted to adolescents. Issue 7 (10th September 2015) - Tabacchi, Garden; Filippi, Anna Rita; Amodio, Emanuele; Jemni, Monèm; Bianco, Antonino; Firenze, Alberto; Mammina, Caterina
Abstract: Objective: The present work is aimed at meta-analysing validity studies of FFQ for adolescents, to investigate their overall accuracy and variables that can affect it negatively. Design: A meta-analysis of sixteen original articles was performed within the ASSO Project (Adolescents and Surveillance System in the Obesity prevention). Setting: The articles assessed the validity of FFQ for adolescents, compared with food records or 24 h recalls, with regard to energy and nutrient intakes. Subjects: Pearson's or Spearman's correlation coefficients, means/standard deviations, kappa agreement, percentiles and mean differences/limits of agreement (Bland–Altman method) were extracted. Pooled estimates were calculated and heterogeneity tested for correlation coefficients and means/standard deviations. A subgroup analysis assessed variables influencing FFQ accuracy. Results: An overall fair/high correlation between FFQ and reference method was found; a good agreement, measured through the intake mean comparison for all nutrients except sugar, carotene and K, was observed. Kappa values showed fair/moderate agreement; an overall good ability to rank adolescents according to energy and nutrient intakes was evidenced by data of percentiles; absolute validity was not confirmed by mean differences/limits of agreement. Interviewer administration mode, consumption interval of the previous year/6 months and high number of food items are major contributors to heterogeneity and thus can reduce FFQ accuracy. Conclusions: The meta-analysis shows that FFQ are accurate tools for collecting data and could be used for ranking adolescents in terms of energy and nutrient intakes. It suggests how the design and the validation of a new FFQ should be addressed.